The RIN-MC Fusion of MADS-Box Transcription Factors Has Transcriptional Activity and Modulates Expression of Many Ripening Genes. Issue 1 (13th November 2017) - Li, Shan; Xu, Huijinlan; Ju, Zheng; Cao, Dongyan; Zhu, Hongliang; Fu, Daqi; Grierson, Donald; Qin, Guozheng; Luo, Yunbo; Zhu, Benzhong
Abstract : Tomato RIN-MC fusion plays a negative role in ripening and encodes a chimeric transcription factor that modulates the expression of many ripening genes, thereby contributing to the rin mutant phenotype. Abstract: Fruit development and ripening is regulated by genetic and environmental factors and is of critical importance for seed dispersal, reproduction, and fruit quality. Tomato ( Solanum lycopersicum ) ripening inhibitor ( rin ) mutant fruit have a classic ripening-inhibited phenotype, which is attributed to a genomic DNA deletion resulting in the fusion of two truncated transcription factors, RIN and MC . In wild-type fruit, RIN, a MADS-box transcription factor, is a key regulator of the ripening gene expression network, with hundreds of gene targets controlling changes in color, flavor, texture, and taste during tomato fruit ripening; MC, on the other hand, has low expression in fruit, and the potential functions of the RIN-MC fusion gene in ripening remain unclear. Here, overexpression of RIN-MC in transgenic wild-type cv Ailsa Craig tomato fruits impaired several ripening processes, and down-regulating RIN-MC expression in the rin mutant was found to stimulate the normal yellow mutant fruit to produce a weak red color, suggesting a distinct negative role for RIN-MC in tomato fruit ripening. By comparative transcriptome analysis of rin and rin 35S :: RIN-MC RNA interference fruits, a total of 1, 168 and 1, 234 genes were identified as potential targets of RIN-MC activation and inhibition. Furthermore, the RIN-MC fusion gene was shown to be translated into a chimeric transcription factor that was localized to the nucleus and was capable of protein interactions with other MADS-box factors. These results indicated that tomato RIN-MC fusion plays a negative role in ripening and encodes a chimeric transcription factor that modulates the expression of many ripening genes, thereby contributing to the rin mutant phenotype.